PENGARUH LABELISASI HALAL, HARGA DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN MELALUI KEPUSAN PELANGGAN (Studi pada Konsumen Kosmetik Sariayu di Kota Semarang) - Novie Putri Anggraini; Sri Suryoko (Universitas Diponegoro, 2018)
The cosmetics industry in Indonesia is currently growing rapidly. Cosmetics is an alternative choice that can be used by consumers to meet the secondary needs and to beautify themselves. Sariayu is one of the products that have been labeled halal. With the diverse selection of cosmetic products in Indonesia provides an opportunity for consumers to evaluate and choose which products to buy that ultimately trigger the occurrence of brand switching. The purpose of this study is to examine the direct and indirect effects of halal labeling, price, product quality, customer satisfaction and customer loyalty. This type of research is explanatory research, with a sample of 100 female respondents in Semarang city who use cosmetic products at least one year. Sampling technique using p urposive sampling. Were collected through questionnaires. Data analysis method used by Partial Least Square (PLS) analysis, mediation / intervening test by using Variance Accounted For (VAF) and Fit Model Indicator by using WarpPLS 6.0 Application. Based on the results of calculation analysis WarpPLS can be explained that the results of direct impact test between halal labeling, price, product quality to customer satisfaction in this research model showed the results of positive and significant influence. The result of direct impact test between halal labeling, price, product quality and customer satisfaction to customer loyalty in this research model show result of positive and significant effect. The result of indirect effect test between halal labeling, price and product quality to customer loyalty through customer satisfaction also show the result of positive and significant influence. The influence of customer satisfaction as the mediating variable in this research model is parsial mediation. Suggestions include improving the quality of the product to make the durability of cosmetics more durable, keep innovating related product packaging to be more attractive and able to protect the product well.